The Wonderful Visit. - Wells, H. G. (Herbert George), 1866-1946 (Open Road Media Sci-Fi & Fantasy, 2015)
An angel comes to Earth in this fantastical tale by H.G. Wells When a fallen angel appears in the skies of southern England, the vicar of a small town mistakes the winged being's dazzling plumage for that of a bird and shoots him down. This is only the first misfortune to befall "Mr. Angel," as he comes to be known. "Neither the Angel of religious feeling nor the Angel of popular belief," this celestial visitor quickly draws the ire of the village folk. But as time goes on, the angel becomes more and more human. His wings atrophy, and much to his surprise, he finds himself falling in love.